Fertility and rural electrification in Bangladesh - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2020)
We use contemporaneous and retrospective panel datasets to examine the household-level relationship between fertility and access to electricity in Bangladesh. We find that access to electricity reduces fertility by about 0.2 children over a period of five years or total fertility rate by about 1.2 in most estimates. This finding is robust with respect to the choice of the estimation method, the choice of sample, and potential presence of endogeneity. The finding also corroborates the theoretical predictions on time use and consumption pattern derived from our model of electrification and fertility. The results also suggest that television is an important impact channel. The study findings underscore the importance of examining a broad and long-term impact of rural electrification and possibly other infrastructure interventions.